1995
DOI: 10.1089/thy.1995.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Doses of Thyroxine Do Not Accelerate Age-Related Bone Loss in Late Postmenopausal Women

Abstract: To examine whether suppressive doses of thyroxine have any adverse effects on bone, we evaluated various bone metabolic markers (lectin-precipitated alkaline phosphatase, osteocalcin, carboxyl-terminal region of type I collagen propeptide, tartrate-resistant alkaline phosphatase, and urinary excretion of hydroxyproline and pyridinium crosslinks), incidence of vertebral deformity, total body and regional (lumbar spine and radius) bone mineral densities (BMDs), and rates of bone loss in 24 late postmenopausal (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Premenopausal n ¼ patients and nonsuppressed patients (39). We found four patients in this group (7%) with one or more vertebral fractures defined as a reduction of 20% or more of the anterior, middle or posterior height.…”
Section: Female Malementioning
confidence: 83%
“…Premenopausal n ¼ patients and nonsuppressed patients (39). We found four patients in this group (7%) with one or more vertebral fractures defined as a reduction of 20% or more of the anterior, middle or posterior height.…”
Section: Female Malementioning
confidence: 83%
“…The majority of study populations had undergone total or near TT followed by RAI and THST. In all but 6 studies,25,2731 the control groups were comprised of healthy euthyroid-matched individuals or local reference populations. In 2 studies,28,30 the control group suffered from benign thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies examining the effects of LT4 therapy on bone in patients with DTC have revealed conflicting outcomes [9][10][11][12]. There are three explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the varying duration of TSH suppression among studies might have contributed to the differences [9]. Changes in the vertebral BMD among patients with suppressed TSH during the first year following initiation of LT4 therapy were higher than in subsequent years [10,14]. Even appropriate LT4 replacement therapy without TSH suppression could lead to bone loss during the first year of treatment [15].…”
Section: Discussionmentioning
confidence: 99%